Efetividade de uma cartilha educativa na promoção do estilo de vida saudável para pessoas com HIV - Lima, Maria Amanda Correia (2021)
With the advent of antiretroviral therapy (ART), HIV infection has become a chronic health condition, and care previously directed only to opportunistic infections has also started to focus on Chronic Noncommunicable Diseases (CND), making the practices of health promotion relevant to People Living with HIV (PLHIV). The general objective of this study was to evaluate the effectiveness of the educational booklet entitled “My booklet of motivation for change! Practices to promote a healthy lifestyle” in promoting healthy lifestyle in PLHIV. This is a randomized controlled trial, held between January 2019 and July 2020. The study population consisted of PLHIV undergoing outpatient follow-up, with a calculated sample of 75 participants for the intervention group and 75 for the control group. Inclusion criteria: PLHIV aged 18 or over, both sexes, on ART for at least six months, score equal to or greater than 35 points on the Health Literacy Scale, and their own landline or cell phone. Exclusion criteria: pregnancy, incapacitating mental illness, homelessness, collective shelter or deprivation of liberty. Discontinuity criteria: loss of follow-up, impossibility of telephone contact and death. Participants were recruited from the infectology clinic at the Hospital Universitário Walter Cantídio (HUWC) in Fortaleza-CE. Data collection took place in four moments: baseline assessment (in person) and reevaluations of two, four and six months (by telephone). After baseline assessment, the intervention group read the booklet in the presence of the researcher, taking it home for fortnightly reading, and the control group received standard care from the institution. The instruments used were: Sociodemographic, Clinical, Epidemiological and Risk Factors Form for NCD in PLHIV, Individual Lifestyle Profile Scale (PEVI), Knowledge, Attitude and Practice Survey (CAP), and Compliance Assessment Questionnaire Antiretroviral Treatment (CEAT-VIH). The project was registered in the Brazilian Registry of Clinical Trials (Rebec), and followed the guidelines of the Consolidated Standards of Reporting Trials (CONSORT). In statistics, non-parametric analysis of variance of repeated measures was used, based on the approach of transforming aligned posts, with the statistical software R, version 3.2.2. The study concluded a total of 70 PLHIV in the intervention group and 74 in the control group. The educational booklet improved the patients' lifestyle, assessed using the PEVI Scale in the reevaluations of two (P<0.001), four (P<0.001) and six months (P<0.001) when compared to baseline and control. In the analysis of the CAP survey, in the Knowledge item, there was no statistical difference between the intervention and control groups, but the contrast analysis pointed out that the impact of the booklet on knowledge may have occurred late, although it showed a gradual increase at each moment of evaluation. In the Attitude item, the intervention with the booklet implied a significant difference between the intervention and control groups in the reevaluations of two (P<0.001) and four months (P=0.002) when compared to the baseline evaluation. In the Practice item, the booklet provided a statistically significant difference (P<0.001) in the intervention group at the expense of control in the reevaluations of two, four and six months compared to baseline. As for the analysis of CEAT-VIH, the intervention group had improved adherence to ART when compared to the baseline assessment (P<0.001) and the control group (P<0.001). It was concluded that, in general, the booklet had an educational impact and was effective in promoting a healthy lifestyle in PLHIV, which can be used by the multiprofessional team in a complementary way in health monitoring consultations, especially for patients with limited technological access.